2019
DOI: 10.1111/ijac.13394
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial neural network optimization for resilient ceramic parts fabricated by direct ink writing

Abstract: Geometries of ceramic parts for high-temperature sealing have great influence on their compression-resilience behaviors. In this work, an accurate and large-scale artificial neural network (ANN) was established to match the relationship between structural parameters and mechanical properties of ZrO 2 parts fabricated by 3D printing. Four geometry parameters of the designed ZrO 2 parts were imported as input and apparent Young's modulus and maximum deformation simulated by finite element method (FEM) were impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Fan Y's research team found that the geometry of high-temperature sealed ceramic parts has a significant impact on their compressive resilience performance, so an accurate and large-scale artificial neural network was built to match the relationship between structural parameters and mechanical properties of ZrO 2 parts fabricated through 3D printing. The prediction results show that the combination of artificial neural network and finite element is a better method to optimize the structure and guide the 3D printing method to fabricate complex ceramic parts [24]. Han X et al proposed a fast, efficient and convenient method to optimize the shape design of centrifugal pump impeller and worm housing by combining genetic algorithm and back propagation neural network.…”
Section: Related Workmentioning
confidence: 99%
“…Fan Y's research team found that the geometry of high-temperature sealed ceramic parts has a significant impact on their compressive resilience performance, so an accurate and large-scale artificial neural network was built to match the relationship between structural parameters and mechanical properties of ZrO 2 parts fabricated through 3D printing. The prediction results show that the combination of artificial neural network and finite element is a better method to optimize the structure and guide the 3D printing method to fabricate complex ceramic parts [24]. Han X et al proposed a fast, efficient and convenient method to optimize the shape design of centrifugal pump impeller and worm housing by combining genetic algorithm and back propagation neural network.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with traditional machining methods, additive manufacturing has recently provided a new resolution for these problems [8,9]. As reported, the 3D printing technologies applicable to ZrO2 ceramics mainly include stereolithography (SLA) [10], direct ink writing (DIW) [11], digital light processing (DLP) [12], fused deposition molding (FDM) [13], and selective laser sintering/melting (SLS/SLM) [14,15]. The SLA technology provides not only a smoother surface finish, but also an improved precision feature in production, which is suitable for fabricating custom-designed dental implants.…”
Section: Introductionmentioning
confidence: 99%